Necessity entrepreneurship : getting beyond the binary - Oliver, Amalya L.; Sydow, Jörg; Cohendet, Patrick (Research in the sociology of organizations ;, 2025)
Necessity entrepreneurship is broadly understood as the identifying and seizing of business opportunities to address basic needs such as food and shelter. This volume proposes new ways of seeing, theorizing, and researching necessity entrepreneurship.